Kemampuan Berpikir Kreatif dan Pemecahan Masalah Siswa melalui Penerapan Model Project Based Learning - Rahmazatullaili Rahmazatullaili; Cut Morina Zubainur; Said Munzir (Universitas Syiah Kuala, 2019)
The purpose of the mathematics learning basically to increase three aspects that are how to thinking and reasoning, to developing the ability of problem solving and to developing the ability of communication. But the fact is many students of Madrasah Tsanawiyah in Banda Aceh haven’t got those three aspects, especially to thinking and to solve the problem. It happens because the mathematics learning that teaches by the teacher didn’t implicate the student actively and didn’t give the chance to the student to solve the problem with some ways to solve, so the ability of creative thinking and the problem solving of the students is not optimal. Cause of that implemented the learning which is help the student in develop the idea or the strategy and increase the activity that is the learning of the project based learning model. The purpose of this research is to knowing the ability of creative thinking and problem solving of the student after applying project based learning model comparing with before applying project based learning model and correlation between the ability of creative thinking and problem solving. This research is the experimental research with the research design one-group pretest-postt test group design. Population of this research is the students of Madrasah Tsanawiyah Swasta Darul Ulum Banda Aceh, and the sample of this research is the students in grade second-eight (VIII-2). Instrumental of this research consisted the test of the ability of creatively thinking and problem solving. Data Analyze does with quantitative using the t-test which is paired samples T-Test to testing the difference of the score that is got by the students before the test and after the test. The result of this research shows that the ability of the creative thinking and problem solving of the student after applying the project based learning model is better than before applying the project based learning model. Besides that, there is the correlation between the creative thinking abilityand problem solving of the student that is learnt through applying the project based learning. The correlation of ability of creative thinking and problem solving is in sufficient category.